PKM Improving Capability of Madrasah Teachers in Implementing Classroom Research in Probolinggo - Moh. Fachri; Yuni Safitri; Yuni Permata Sari; Nurul Jamila; Intan Permata Sari; Rohmah Rohmah (Universitas Nurul Jadid, 2021)
Teachers as a professional staff should have the ability to analyze the problem on the kids, and it has become the study to solve problems students through classroom research. But most teachers have not known enough to develop a research proposal class action. Teachers' low-level knowledge in doing classroom research is one of the problems in contemporary education. This community service is to equip teachers to implement classroom research. This study aims to make most teachers understand classroom research and figure out how to arrange good classroom research. The benefit of this community service was that teachers were able to make proposals/proposals for classroom research good and under the proper format and give the idea of a follow-up to teachers after composing classroom research proposals. The purpose for teachers on the procedure writing classroom research is that they are motivated to write classroom research. As for the result of assistance and changes in conclusion as follows: 1) able to identify problems in learning in class. School teachers can also solve a problem by solutions that they consider strategic through learning innovative methods. 2) school teachers can describe identification problems in the background problems and determine the title research will be classroom research. School teachers also have been able to prepare the theory according to the title research will be implemented. 3) school teachers can arrange research procedures consisting of planning, research, observation, and reflection. 4) school teachers can learn according to learning preparation every cycle. 5) school teachers can arrange research reports on classroom action in the scientific article.